INOVASI PRODUK, KUALITAS, DAN HARGA SEBAGAI DETERMINAN MINAT BELI KONSUMEN KERAJINAN SARUNG TENUN SAMARINDA - Joana Oktavia Sapan; Muhammad Zaini (ITB AAS Indonesia Surakarta, 2026)
Samarinda Weaving Sarongs as a traditional handicraft product of East Kalimantan faces various challenges in maintaining its existence and competitiveness in the modern market. Changes in people's consumption patterns that increasingly lead to efficiency, digital trends, and a preference for instant products have led to a decrease in interest in tradition-based products. The low level of innovation and digitalization among SMEs is also a problem in itself. Based on the theory of planned behavior, a person's interest in buying is determined by their attitude towards behavior, subjective norms, and perception of behavior control (Ajzen, 1991). This study aims to analyze the influence of product innovation, product quality, and price on consumer buying interest, using a quantitative approach with explanatory research methods. The sample totaled 100 respondents. Primary data were collected through questionnaires with Likert scale measuring tools and analyzed using validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, t-tests, F tests, and determination coefficients (R²). The results of the study show that product innovation, product quality, and price have a positive effect on consumer buying interest, partially or simultaneously. The author recommends the Samarinda Woven Sarong IKM to create traditional motifs with a modern touch, consistent in quality using premium materials and quality control, determine pricing strategies for various market segments, and expand digital marketing. Keywords: Product Innovation; Product Quality; Price; Consumer Buying Interest; Samarinda Weaving Sarong.